An anisotropic plasticity model for quasi-brittle composite shells - Lourenço, Paulo B. (1997)
A material model for the analysis of anisotropic plates and shells is described. The prepared plasticity model includes two different yield criteria: one to represent tensile failure and another to represent compressive failure, The model describes adequately the failure behaviour of cohesive-frictional materials, with large differences in the magnitude of uniaxial tensile and compressive strength. Additionally, independent elastic and inelastic behaviour can be described along each material axis. To validate the numerical implementation, a comparison between experimental and numerical results in masonry shell panels is also presented.